Enantioselective synthesis of indole‐based unnatural β‐Alkynyl α‐amino acid derivatives via chiral phosphoric acid catalysis. Issue 4 (7th February 2022) - Woldegiorgis, Alemayehu Gashaw; Gu, Haorui; Lin, Xufeng
Abstract: The synthesis of unnatural α ‐amino acid derivatives has attracted considerable interest in recent years, as they are ubiquitous in protein synthesis and peptide‐based drug discovery. Herein, we reported the chiral phosphoric acid catalyzed asymmetric reaction of indoles with β, γ ‐alkynyl‐ α ‐imino esters for the enantioselective synthesis of unnatural indole‐based α ‐amino acid derivatives. This asymmetric organocatalysis protocol enables efficient synthesis of unnatural α ‐amino acid derivatives with a tetrasubstituted stereogenic center and an alkyne moiety with up to 99% yield and 98% ee, resulting in operationally simple conditions, short reaction time, and broad substrate scope. Abstract : Asymmetric organocatalysis protocol provides enantioselective synthesis of unnatural indole‐based α ‐amino acid derivatives with a tetrasubstituted stereogenic center and an alkyne moiety.